Inducing Flow Velocities to Manage Fish Reproduction in Regulated Rivers. (February 2021) - Chen, Qiuwen; Zhang, Jianyun; Chen, Yuchen; Mo, Kangle; Wang, Jun; Tang, Lei; Lin, Yuqing; Chen, Lei; Gao, Yong; Jiang, Wei; Zhang, Yuxin
Graphical abstract: Highlights: Lab and field experiments are conducted to explore fish reproduction with flow velocity. Reproduction considers not only spawning, but also fertilizing, hatching and surviving. A compromised optimal velocity range is identified for Chinese carps reproduction. Engineering application to adaptive reservoir management showed promising potentials. Abstract: Conservation of endangered or economic fish and control of invasive fish is a great challenge of hydraulic engineering worldwide. Flow velocity has been recognized to affect the spawning of fishes delivering drifting eggs in rivers. However, solid scientific supports and associated mechanisms to establish quantitative relations between flow velocity and fish reproduction, taking into account spawning, fertilizing, hatching, as well as surviving, are lacking. In this paper, we quantified the relationship between flow velocity and reproduction of Chinese carps through both lab and field experiments. The results showed that a minimum velocity was required to trigger Hypophthalmichthys molitrix ( H. molitrix ) releasing eggs, and a velocity range was preferred to sustain spawning activity. However, the embryo incubation and larvae development of H. molitrix were found to be inhibited with the increase in flow velocity. Considering the requirements of spawning and hatching, as well as larvae surviving, an optimized flow velocity processes was identified for the reproduction of H. molitrix in rivers. These findings were of great significance to the adaptive operation of reservoirs to create reasonable and precise ecological flows for managing fish reproduction, as shown by the promising results in the engineering application to the Three Gorges Reservoir.